Loss of CASK Accelerates Heart Failure Development. Issue 8 (17th February 2021) - Mustroph, Julian; Sag, Can M.; Bähr, Felix; Schmidtmann, Anna-Lena; Gupta, Shamindra N.; Dietz, Alexander; Islam, M.M. Towhidul; Lücht, Charlotte; Beuthner, Bo Eric; Pabel, Steffen; Baier, Maria J.; El-Armouche, Ali; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Increased myocardial activity of CaMKII (Ca/calmodulin-dependent kinase II) leads to heart failure and arrhythmias. In Drosophila neurons, interaction of CaMKII with CASK (Ca/CaM-dependent serine protein kinase) has been shown to inhibit CaMKII activity, but the consequences of this regulation for heart failure and ventricular arrhythmias are unknown. Objective: We hypothesize that CASK associates with CaMKII in human and mouse hearts thereby limiting CaMKII activity and that altering CASK expression in mice changes CaMKII activity accordingly, with functional consequences for contractile function and arrhythmias. Methods and Results: Immunoprecipitation revealed that CASK associates with CaMKII in human hearts. CASK expression is unaltered in heart failure but increased in patients with aortic stenosis. In mice, cardiomyocyte-specific knockout of CASK increased CaMKII-autophosphorylation at the stimulatory T287 site, but reduced phosphorylation at the inhibitory T305/306 site. Knockout of CASK mice showed increased CaMKII-dependent sarcoplasmic reticulum Ca leak, reduced sarcoplasmic reticulum Ca content, increased susceptibility to ventricular arrhythmias, greater loss of ejection fraction, and increased mortality after transverse aortic constriction. Intriguingly, stimulation of the cardiac glucagon-like peptide 1 receptor with exenatide increased CASK expression resulting in increased inhibitory CaMKII T305 phosphorylation, reduced CaMKII activity, and reduced sarcoplasmic reticulum Ca leak in wild type but not CASK-KO. Conclusions: CASK associates with CaMKII in the human heart. Knockout of CASK in mice increases CaMKII activity, leading to contractile dysfunction and arrhythmias. Increasing CASK expression reduces CaMKII activity, improves Ca handling and contractile function.